Securing our energy future: three international perspectives on microgrids and distributed renewables as a path toward resilient communities. (3rd April 2017) - Jones, Kevin B.; James, Mark; Mastor, Roxana-Andreea
ABSTRACT: This paper will examine three diverse microgrid cases in the US, Canada, and the European Union. The paper will explore how microgrids can help build resilient communities, facilitate distributed renewable energy, and ultimately lead to a secure energy future. The cases will include both urban and remote settings and compare the social, legal, and policy lessons learned from these cases to advance microgrid policy for long-term community resilience.